Short film project nina nak kahwin? : breaking the fourth wall, an existentialist approach / Qistina Yusof - Yusof, Qistina (Faculty of Film, Theatre and Animation, 2015)
This is a project-based thesis that studies breaking the fourth wall from an existentialist approach through the short film Nina Nak Kahwin?. Although there have been adequate of studies on breaking the fourth wall from a spectatorship standpoint, there is a lack of appreciation in how breaking the fourth wall in a film can exude aesthetic and philosophical values. Therefore in this dissertation, I conduct a qualitative study on in-depth analysis based on existential concepts illuminated by renowned philosophers Søren Kierkegaard and Jean Paul Sartre of the human condition of being and anxiety and incorporating in the analysis of Tom Brown’s examples of breaking the fourth wall agency, intimacy and honesty performed by the main character Nina. Therefore, in this study, I extract existential qualities through the direction and narration style of breaking the fourth wall in this film.